SAT0163 IMMUNOSUPPRESSANT WITHDRAWAL AFTER REMISSION ACHIEVEMENT IN LUPUS NEPHRITIS: EFFECT ON FLARE OCCURRENCE. (2nd June 2020) - Zen, M.; Gatto, M.; Benvenuti, F.; Saccon, F.; Larosa, M.; Iaccarino, L.; Doria, A.
Abstract : Background: Whether and when immunosuppressive therapy may be safely withdrawn in patients with lupus nephritis (LN) is still poorly defined. Indeed, there is no clear agreement about the optimal duration of maintenance treatment. Objectives: We aimed at assessing the rate and predictors of flare after IS withdrawal in patients with LN in remission. Methods: Patients with systemic lupus erythematosus (SLE) (ACR criteria) and biopsy-proven LN diagnosed between 1990 and 2019, ever treated with IS and currently in follow-up were considered. IS discontinuation was defined as the complete withdrawal of any immunosuppressive drug in patients in remission. Remission was defined as normal serum creatinine, proteinuria <0.5 g/24h, inactive urine sediment, and no extra-renal SLE activity (clinical SLE Disease Activity Index [c-SLEDAI]-2K=0) on a stable immunosuppressive and/or antimalarial therapy and/or on prednisone ≤5 mg/day. Flares were defined according to SLEDAI Flare Index; renal flare was defined as an increase of proteinuria >0.5 g/24h requiring an increase in corticosteroid therapy or the reintroduction of IS. Predictors of a subsequent flare were analyzed by multivariate logistic regression analysis. Results: Out of 456 SLE patients regularly followed-up, 206 (45.1%) had LN and were considered in our study. Eighty-three patients (40.3%) discontinued IS after remission achievement (Table 1 ). After stopping therapy, patients were followed for a mean±SD of 99±77 months (range 12-378). Nineteen patients (22.8%) developed a flare after IS discontinuation, after a mean±SD follow-up of 78±68 months (range 7-312), and were re-treated; among them, 6 patients (7.2%) experienced a renal and 13 (15.6%) an extra-renal flare. Compared to patients who flared, patients in persistent IS-free remission had longer remission before IS withdrawal (51.2±31.5 vs. 29.3±16.5 months, p<0.001), and continued antimalarials after IS discontinuation (p=0.005). No differences in flare occurrence according to the type of IS discontinued were found. At multivariate analysis, therapy with antimalarials was the strongest protective factor against disease flare (OR 0.06, 95% CI 0.11-0.41, p=0.004) (Table 2 ). At last follow-up, mean±SD SLEDAI-2K was 3.1±2.8 and 1.5±1.6 in patients who experienced or not a flare after IS discontinuation, respectively (p=0.058), Indeed, 10/19 patients (52.5%) who developed a flare re-achieved remission. Conclusion: Based on our experience, withdrawal of IS is feasible in selected patients with LN, i.e. patients who achieved stable remission and received maintenance therapy with antimalarials. Patients who experience new flares can re-achieve remission with an appropriate treatment. Disclosure of Interests: Margherita Zen Speakers bureau: BMS, Ely Lilly, Janssen, GSK, Mariele Gatto Speakers bureau: GSK, Francesco Benvenuti: None declared, Francesca Saccon: None declared, Maddalena Larosa: None declared, Luca Iaccarino Speakers bureau: GSK, Pfizer, Janssen, Novartis, Andrea Doria Consultant of: GSK, Pfizer, Abbvie, Novartis, Ely Lilly, Speakers bureau: UCB pharma, GSK, Pfizer, Janssen, Abbvie, Novartis, Ely Lilly, BMS